Studies of Yeasts Isolated from Soil as Cellulose Decomposers and Phosphate Solvents - Putra, Gading Gunawan; salsabila, Syarifah salsabila; Rahmawati, Hanif Nur; fatimah (Universitas Airlangga, 2023)
The identification of CMCase (Carboxymethylcellulase) and PMEase (Phosphomonoesterase) enzyme activities from yeast genera that produce cellulase and phosphatase is crucial for identifying potential genera that could aid in the development of biofertilizers, serving as an environmentally friendly alternative to chemical fertilizers. This study is based on a review of articles and journals for data collection. The review revealed that the yeast genus Rhodosporidium (specifically Rhodosporidium paludigenum Y08RA29) is a promising cellulolytic yeast, with CMCase activity approaching 0.500 units. Meanwhile, the potential phosphate-solubilizing yeast genus is Candida (Candida sp. 3), with PMEase activity ranging from 0.05 to 0.06 units.